Oscar Wilde and la critique impressionniste - Richard Hibbitt (Cahiers Victoriens et Edouardiens)
It is well known that Wilde’s aestheticism was based not only on the ideas of Arnold, Pater, Ruskin and Swinburne but also on his reading of French writers including Baudelaire, Flaubert, Gautier and Mallarmé. However, Wilde’s writing also suggests an interesting affinity with other nineteenth-century French writers such as Ernest Renan, Anatole France and Jules Lemaître. This affinity is particularly evident in Wilde’s belief that criticism should be viewed as a creative art based on the critic’s personal impressions.This essay takes its cue from Téodor de Wyzewa’s dismissive appraisal of Wilde as a mere imitator of French aestheticism, arguing that Wilde should be aligned with the sceptical dilettantism that Paul Bourget identifies in the work of Ernest Renan. It shows how Wilde’s views of criticism in the essays collected in Intentions are prefigured by Anatole France and Jules Lemaître, and how the dialogic discussion of art in ‘The Critic as Artist’ itself prefigures a real-life debate between France and the conservative critic Ferdinand Brunetière, who rejected the ‘subjective’ approach as ‘impressionist criticism’. The aim is to show how Wilde’s view of criticism combined aestheticism with a profound belief in the value of paradox and inconsistency as epistemological tools.